CUSTOMERS’ PERCEPTIONS OF SERVICE QUALITY DIMENSIONS IN THE INDONESIAN BANKING INDUSTRY: AN EMPIRICAL STUDY - Ananda Sabil Hussein; Raditha Hapsari (Faculty of Economics and Business, Universitas Gadjah Mada, 2015)
This study aims to investigate the dimensions of hierarchical service quality in the area of the banking sector as well as to determine its relationships with other constructs, namely corpo-rate image and customer loyalty. One hundred and eleven respondents participated in this study. Partial Least Squares were employed to analyse the data. The inner and outer model evaluations showed that the proposed model was robust. This study found that the interaction quality, outcome quality and physical quality were the dimensions of service quality which were formed in the hierarchical model. In addition, this study indicated that service quality was a robust determinant of corporate image and customer loyalty in the banking sector. Similar to service quality, corporate image was also found to be an essential predictor of customer loyalty as well as the mediator between service quality and customer loyalty. To enhance the under-standing of service quality in the banking sector, further studies might add additional constructs such as brand engagement, perceived value, and customer experience.Keywords: service quality, image, loyalty, bank